TERHAMBATNYA PEMEROLEHAN BAHASA PADA ANAK USIA 4-6 TAHUN - Ahmad Aji Fashihudin; Devi Mariyani; Sindi Quratul Uyun; Mardiah Hayati (CV. Denasya Smart Publisher, 2024)
Parents should pay attention if their children experience delays in acquiring their first language. This phase functions as a provision so that a child can communicate well in his environment in the future. Therefore, there are several things that can become obstacles in children's language acquisition and must be given special attention. Based on these facts, this research aims to explain the factors that hinder the acquisition of a first language in children aged 4 to 6 years and describe the situation of these children. This research uses a qualitative descriptive method with three selected subjects. To improve data analysis, the method used in the research was the interview method conducted on the children's parents. The results of the research show that there are several factors that cause delays in children's language acquisition, based on a survey of 3 children that has been carried out, each factor has the following percentages 1) The use of gadgets is 66.7% of the 3 children, 2) The genetic factor is 33.3 % of 3 children, 3) The factor of lack of two-way interaction with parents and the environment around 100% of 3 children, 4) Then the factor of introducing foreign languages too early in children 66.7% of 3 children, and 5) The factor of ADHD sufferers 33.3% of 3 children. Based on these factors, parents must pay more attention and increase intensity in helping children communicate in their first language.